Some Issues Concerning the Appointment and Payment of Monthly Government Benefits to a Person, Suspended from Post for Beinga Suspected (Accused Person, Person on Trial) in the Criminal Judicial Proceeding in Russia and Kazakhstan: Legal and Law Application Aspects - Natal'ya S. Kashtanova (Сибирское юридическое обозрение, 2017)
In the present research paper on the basis of a comprehensive analysis of the applicable Russian and Kazakhstan criminal and procedural legislation the Author discusses the main features of the legal nature of monetary compensation assigned to suspended persons, suspected in committing a crime (accused persons, persons on trial). In particular, the research paper examines the regulations allowing the court, at first sight, not to solve the issue (inthe corresponding prescript) regarding this measure of government social support. The Author differentiates between two options: procedural expenses for the monthly state benefit to the suspended person are to be paid by the financial authority of the corresponding body of pre-trial investigation or by the Department of the Judicial Board of the Supreme Court of a particular subordinate entity of the Russian Federation. With regard to the mentioned questions the Author has studied the experience of law enforcement; he also provides the legal positions of the Constitutional Court of the Russian Federation. A comment is made about certain shortcomings of article 114 of the Criminal Procedural Code of the Russian Federation. Some definite practical recommendations and ways of improving Russian criminal law of procedure are suggested.